Measuring the Information Society in Europe: From Definitions to Description - Timo Hirvonen; Lauri Frank (European Regional Science Association (ERSA), 2006)
Information Society (IS) indicators describe the level of information society development achieved in a particular society in quantitative terms. They can serve a range of purposes related to providing a view of the society's state: for example, following the evolution of IS or benchmarking IS with other territories. By considering changes over time, IS indicators also comprise a critical tool in the monitoring, evaluation and improvement of IS policy. Inevitably, the primary benefit of indicators lies in this capacity to guide policy-makers into proactive thinking i.e. to focus their attention on future priorities. The aims of this article are to examine how the evolution of the information society has been measured, and to relate European territories with each other by these measures. Constructing a comprehensive set of IS indicators requires a sound definition of the Information Society to establish meaningful benchmarks and to measure change. The task becomes complicated as it seems that IS is more or less 'undefined' at the moment. This means that IS is what one wants it to be: countries held as "information societies" are those countries, which people think of being such – and not defined by, for example, achieving a level measured by some quantitative IS-related indicators. Tentative results show that despite this lack of a clear and single definition of Information Society (IS) one can derive some conclusions about what IS consists of by taking a look at previous IS projects having collected IS indicators. They indicate three different levels of IS. These levels range from the narrow technological and the intermediate techno-economic definitions to the broad, all-inclusive IS definition. The indicators used to measure IS can also be grouped by a lifecycle model. While there seems to be a lack of available consistent territorial data on IS, there is plenty of data available on the national level. Using this data and background variables the European state of IS is analyzed from a territorial perspective. This article is an outgrowth of the ESPON project "Identification of Spatially Relevant aspects of the Information Society".
Keywords: 330